Chemical weathering rates, erosion rates and mobility of major and trace elements in a boreal granitic till - Land, Magnus; Öhlander, Björn (Luleå tekniska universitet, 2000)
Chemical weathering rates and erosionrates of granitic till in northern Sweden have beenestimated. The present-day chemical weathering rate iscompared with the long-term average weathering ratesince the last deglaciation approximately 8,700 yearsago. Also, the present-day release rates of major andtrace elements due to chemical weathering are comparedwith the mobility of these elements in a spodosolprofile as shown by soil water samples from the vadozezone. The estimation of the past weathering rate isbased on elemental depletion trends in a soil profile(typic haplocryod), whereas the present weatheringrate is based on elemental input/output budgets in asmall catchment . Validerad; 2000; Bibliografisk uppgift: Se hela abstraktet i fulltextdokumentet; 20070316 (pafi)